КОАЛИННИ БОЙИТИШ ТЕХНОЛОГИК ЖАРАЁНИНИ ОПТИМИЗАЦИЯЛАШ АЛГОРИТМИНИ ИШЛАБ ЧИҚИШ - Файзуллаев, Б.А. (SCIENCE and SOCIETY, 2020)
In the article algorithm for optimizing the kaolin enrichment process has been studied. The developed algorithm allows us to estimate the final error based on the method of belonging to a certain class of the theory of fuzzy sets and the gradient method. The dependence of the gradient values was studied on the basis of the redistribution of weights depending on the initial values and the degree of correlation of the distribution of weights.